The tuneable rubberwood: roles of impregnated polymer level. Issue 6 (2nd November 2021) - Meethaworn, Benjama; Khongtong, Sureurg
ABSTRACT: This study exhibits the tuneable rubberwood with the actively controlled properties. Various amounts of polymethyl methacrylate (PMMA) were introduced into rubberwood tissues under the allowed environment. The embedded PMMA resulted to weight gaining up to about 60% and caused an increase in the density from 650 (for untreated rubberwood) to 1060 kg/m 3 (for fully impregnated one). Additionally, scanning electron microscopic images revealed the evidence of the raising of PMMA amounts in the microstructure of treated rubberwood corresponding to the degrees of polymer impregnation. The embedded PMMA, from 0% to about 60% in wood tissues, enhanced water-resistant properties, i.e. the increasing in the surface contact angles for about 20 degrees, the improvement of water absorption for four times and the development of anti-swelling efficiency (ASE) for almost 20%, to the treated rubberwood. Mechanical properties, including shear, compressive and flexural strength of treated rubberwood were also gradually improved when higher levels of PMMA were incorporated into rubberwood. Moreover, the logarithm values of water absorption, ASE, shear strength and compressive strength revealed the linear tendency when the degree of impregnation was raised. This would provide an opportunity of treating rubberwood as a tuneable wood-polymer composite material for the designated applications.